An effective intracellular delivery system of monoclonal antibody for treatment of tumors: erythrocyte membrane-coated self-associated antibody nanoparticles. (21st July 2017) - Gao, Lipeng; Han, Lin; Ding, Xiaoling; Xu, Jiaojiao; Wang, Jing; Zhu, Jianzhong; Lu, Weiyue; Sun, Jihong; Yu, Lei; Yan, Zhiqiang; Wang, Yiting
Abstract: Antibody-based drugs have attracted much attention for their targeting ability, high efficacy and low toxicity. But it is difficult for those intrabodies, a kind of antibody whose targets are intracellular biomarkers, to become effective drugs due to the lack of intracellular delivery strategy and their short circulation time in blood. Human telomerase reverse transcriptase (hTERT), an important biomarker for tumors, is expressed only in cytoplasm instead of on cell membrane. In this study, the anti-hTERT blocking monoclonal antibody (mAb), as the model intrabody, was used to prepare nanoparticles (NPs), followed by the encapsulation of erythrocyte membrane (EM), to obtain the EM-coated anti-hTERT mAb NPs delivery system. The final NPs showed a z -average hydrodynamic diameter of about 197.3 nm. The in vitro cellular uptake by HeLa cells confirmed that compared with free anti-hTERT mAb, the EM-coated anti-hTERT mAb NPs exhibited a significantly increased uptake by tumor cells. Besides, the pharmacokinetic study confirmed that the EM encapsulation can remarkably prolong the circulation time and increase the area under curve (AUC) of NPs in blood. The EM-coated anti-hTERT mAb NPs exhibited a remarkably decreased uptake by macrophages than uncoated NPs, which may be responsible for the prolonged circulation time and increased AUC. Furthermore, the frozen section of tumor tissue was performed and proved that the EM-coated anti-hTERT mAb NPs can be more effectively accumulated in tumor tissues than the free mAb and uncoated NPs. In summary, this study indicated that EM-coated anti-hTERT mAb NPs are an effective delivery system for the long circulation and intracellular delivery of an intrabody, and make it possible for the intracellular biomarkers to become the potential targets of drugs.